Who (Else) Benefits from Electricity Deregulation? Coal Prices, Natural Gas and Price Discrimination - Jonathan E. Hughes; Ian A. Lange (Center for Economic Studies and ifo Institute (CESifo), 2018)
The movement to deregulate major industries over the past 40 years has produced large efficiency gains. However, distributional effects have been more difficult to assess. In the electricity sector, deregulation has vastly increased information available to market participants through the formation of wholesale markets. We test whether upstream suppliers, specifically railroads that transport coal from mines to power plants, use this information to capture economic rents that would otherwise accrue to electricity generators. Using natural gas prices as a proxy for generators' surplus, we find railroads charge higher markups when rents are larger. This effect is larger for deregulated plants, high-lighting an important distributional impact of deregulation. This also means policies that change fuel prices can have substantially different effects on downstream consumers in regulated and deregulated markets.
Keywords: L11; L51; Q48; 330; deregulation; price discrimination; electricity markets; procurement contracts